Barney says, "Please and thank you" - White, Stephen; Grayson, Rick (New York : Barney Pub., 1994)
Barney teaches his friends good manners at a birthday party.
6 13 21 23 27 31
Keywords: Parties -- Fiction; Dinosaurs -- Fiction; Etiquette--Fiction.